Taking a Look into the Culture Shock Experienced by Foreigners at Rumbai, Pekanbaru - Herdi, Herdi; Handayani , Titi (Universitas Lancang Kuning, 2020)
Culture is something that represents a country’s existence. Every country has a different culture because it has its way of life, habit, and custom. This research was aimed to find out the culture shock experienced by foreigners at Rumbai, Pekanbaru. This research was categorised as survey research designed. This research was descriptive qualitative. This research used purposive sampling to get the sample. Three foreigners responded in this research. The data of the study were taken by using observation, interview and field note. The researcher found that there were four stages of culture shock experienced by foreigners and six factors affecting culture shock experienced by foreigners. The first stage of culture shock was euphoria/honeymoon phase because of hospitality, scenery and custom of the host country. The second was the crisis stage, this crisis phase because of cross-culture differences in how people communicate. The third was recovery phases, where they began to accept, to resolve and to adjust their cultural differences. Finally, was the adjustment phase where they were enjoyed and accepted the cultural differences in the new environment. There were six factors affecting culture shock, and they were culture shock on weather, culture shock on food, culture shock on language, culture shock on social life, culture shock on etiquette and culture shock on the dress.